Evolutionary blueprint for host- and niche-adaptation in Staphylococcus aureus clonal complex CC30 - Mcgavin, Martin J.; Arsic, Benjamin; Nickerson, Nicholas N. (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus clonal complex CC30 has caused infectious epidemics for more than 60 years, and, therefore, provides a model system to evaluate how evolution has influenced the disease potential of closely related strains. In previous multiple genome comparisons, phylogenetic analyses established three major branches that evolved from a common ancestor. Clade 1, comprised of historic pandemic phage type 80/81 methicillin susceptible S. aureus (MSSA), and Clade 2 comprised of contemporary community acquired methicillin resistant S. aureus (CA-MRSA) were hyper-virulent in murine infection models. Conversely, Clade 3 strains comprised of contemporary hospital associated MRSA (HA-MRSA) and clinical MSSA exhibited attenuated virulence, due to common single nucleotide polymorphisms (SNP's) that abrogate production of α-hemolysin Hla, and interfere with signaling of the accessory gene regulator agr. We have now completed additional in silico genome comparisons of 15 additional CC30 genomes in the public domain, to assess the hypothesis that Clade 3 has evolved to favor niche adaptation. In addition to SNP's that influence agr and hla, other common traits of Clade 3 include tryptophan auxotrophy due to a di-nucleotide deletion within trpD, a premature stop codon within isdH encoding an immunogenic cell surface protein involved in iron acquisition, loss of a genomic toxin–antitoxin (TA) addiction module, acquisition of S. aureus pathogenicity islands SaPI4, and SaPI2 encoding toxic shock syndrome toxin tst, and increased copy number of insertion sequence ISSau2, which appears to target transcription terminators. Compared to other Clade 3 MSSA, S. aureus MN8, which is associated with Staphylococcal toxic shock syndrome, exhibited a unique ISSau2 insertion, and enhanced production of toxic shock syndrome toxin encoded by SaPI2. Cumulatively, our data support the notion that Clade 3 strains are following an evolutionary blueprint toward niche-adaptation.